Psychological impacts of thyroid cancer diagnosis and treatment—a retrospective study - Liu, Xinjie; Shi, Jianhua; Gu, Hui; Wang, Xueqin (Frontiers in Psychology, 2025)
BackgroundThe psychological impacts of thyroid cancer diagnosis and treatment are poorly understood, despite their significant influence on patient well-being. This study retrospectively evaluated the prevalence, predictors, and longitudinal changes in psychological distress among patients treated for thyroid cancer at Nantong First People’s Hospital from January 2021 to December 2024.MethodsA total of 249 adults diagnosed with thyroid cancer were included in the study, with data extracted from the hospital’s electronic medical records (EMRs). Demographic, clinical, and psychosocial variables were analyzed along with standardized psychological assessment scores, such as the Hospital Anxiety and Depression Scale (HADS), Beck Depression Inventory (BDI), and Generalized Anxiety Disorder-7 (GAD-7). Assessments were conducted at baseline and at 3, 6, and 12 months post-treatment. Descriptive statistics were used to summarize patient characteristics; repeated-measures analysis of variance (ANOVA) was performed to evaluate changes over time; and logistic regression analyses were conducted to identify predictors of severe distress. Missing data were addressed through multiple imputation to ensure the robustness of the analyses.ResultsWe assessed 249 participants with a mean age of 39.5 years (SD = 12.3), ranging from 18 to 50 years. The cohort included 97 men (before andropause) and 152 women (before menopause). Low socioeconomic status was associated with the highest levels of psychological distress at baseline, with HADS-Anxiety scores of 9.8 ± 3.7, BDI scores of 19.7 ± 6.2, and GAD-7 scores of 10.3 ± 3.5. Psychological distress significantly declined over 12 months for all treatment groups (p < 0.001). Logistic regression analysis revealed that advanced tumor stage (OR = 2.47, 95% CI: 1.89–3.23), combined therapy (OR = 1.68, 95% CI: 1.34–2.10), low socioeconomic status (OR = 3.12, 95% CI: 2.45–4.22), and lack of social support (OR = 4.29, 95% CI: 3.12–5.87) were significant predictors of severe psychological distress.ConclusionThyroid cancer diagnosis and treatment had profound psychological impacts, particularly among patients with low socioeconomic status and advanced disease. Psychological distress declined significantly over time, underscoring the importance of early mental health interventions. Addressing psychosocial disparities may enhance overall patient outcomes.